2020
DOI: 10.3390/cancers12092527
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of Early-Stage Hepatocellular Carcinoma: Comparison between Trans-Arterial Chemoembolization and Radiofrequency Ablation

Abstract: Radiofrequency ablation (RFA) is a curative treatment for early-stage hepatocellular carcinoma (HCC) ineligible for surgery or liver transplantation. However, trans-arterial chemoembolization (TACE) might be an alternative when RFA is contraindicated due to structural problems. Here, we aimed to compare their long-term outcomes. Treatment-naive HCC patients fulfilling the Milan criteria who underwent RFA (n = 136) or TACE (n = 268) were enrolled. Complete response (CR) and 5-year recurrence-free survival (RFS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…A total of 15 references were included in the analysis, including four randomized controlled trials [ 7 , 20 22 ] and two retrospective studies [ 12 , 23 ] in the 2- to 3-month group and three randomized controlled trials [ 24 26 ] and six retrospective studies [ 10 , 27 31 ] in the 3- to 4-month group. Of 1940 patients from the 15 included studies, 504 patients were classified into the 2- to 3-month group, and the rest of the 1436 patients were classified into the 3- to 4-month group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 15 references were included in the analysis, including four randomized controlled trials [ 7 , 20 22 ] and two retrospective studies [ 12 , 23 ] in the 2- to 3-month group and three randomized controlled trials [ 24 26 ] and six retrospective studies [ 10 , 27 31 ] in the 3- to 4-month group. Of 1940 patients from the 15 included studies, 504 patients were classified into the 2- to 3-month group, and the rest of the 1436 patients were classified into the 3- to 4-month group.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, RFA potentially provides similar therapeutic effects to liver resection for tumors between 3 and 5 cm in randomized controlled trials [ 7 , 8 ]. However, up to 30% of patients develop tumor recurrence within two years following RFA with complete remission [ 9 , 10 ]. Therefore, surveillance for early detection of recurrence after RFA therapy is a significant approach for long-term survival and better quality of life [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…TACE is the first-line treatment for patients with intermediate-stage HCC. 3 It has been recently reported that patients in their early stages of TACE-based treatment could potentially benefit from the method, 26 , 27 resulting in an improved survival rate. However, complete embolism could only be observed in approximately 20% of the patients with HCC who were subjected to conditions of TACE.…”
Section: Discussionmentioning
confidence: 99%
“…HCC patients who are ineligible for surgery or liver transplantation may choose to undergo radiofrequency ablation (RFA) or microwave ablation (MWA), alternative therapies with a minimal invasiveness (3). RFA and MWA have similar therapeutic effects, complication rates, and rates of residual foci of untreated disease; however, RFA can be applied to tumor ablation with fewer sessions (4) and was recommended for safe and effective first-line treatment of early-stage HCC (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%